Pembelajaran Bahasa dengan Pendekatan Budaya - Abusyairi, Khairy (IAIN Samarinda, 2013)
When the teacher teaches a second language or a foreign language, often times he forgot to convey the culture contained in the language, so the language is often learned the common errors in usage. The learning based culture based on the recognition of culture as a fundamental part of the learning process. Cultural content of Arabic language learning in particular can be integrated in the following stages: a) learning materials, b) the selection and organization of material, c) learning method with a cultural approach, d) evaluation.